2019
DOI: 10.1016/j.cub.2019.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Reward Inhibits Paraventricular CRH Neurons to Relieve Stress

Abstract: Highlights d PVN CRH neurons are rapidly inhibited by natural reward d Reward relieves stress-induced behavioral and hormonal responses d Reward rebalances the synaptic homeostasis of PVN CRH neurons d Reward abolishes stress-induced burst firing in PVN CRH neurons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 52 publications
(59 reference statements)
5
104
0
Order By: Relevance
“…Thus, CRF neurons in the PVN could work as an "interface" to transmit circadian information from the SCN to other brain areas and/or organs that temporally regulate physiological functions. It is also reported that CRF neurons in the PVN exhibited burst firings (37). In the present study, we observed calcium spikes in CRF neurons in the PVN, which was regulated by the GABAergic neurons in the SCN.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, CRF neurons in the PVN could work as an "interface" to transmit circadian information from the SCN to other brain areas and/or organs that temporally regulate physiological functions. It is also reported that CRF neurons in the PVN exhibited burst firings (37). In the present study, we observed calcium spikes in CRF neurons in the PVN, which was regulated by the GABAergic neurons in the SCN.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies have shown that PVN-CRH neurons are able to respond differentially to stimuli with positive or negative valence (Kim et al, 2019; Yuan et al, 2019). Using in vivo fiber photometry to monitor population calcium dynamics, Kim et al (2019) have shown that the activity of PVN-CRH neurons rapidly increases in response to stimuli with negative valence, and decreases when an appetitive stimulus such as food or social interaction is presented.…”
Section: Role Of Hypothalamic Corticotropin (Pvn-crh) Neurons In Strementioning
confidence: 99%
“…Surgical procedures generally followed those from previous studies [26,27]. Briefly, mice were anesthetized by intraperitoneal injection of pentobarbital (100 mg/kg), kept warm (37°C) with an electric heating pad (BrainKing Biotech), and mounted in a stereotaxic holder in order to adjust their skulls to be parallel with the reference panel.…”
Section: Viral Micro-injection and Stereotaxic Surgerymentioning
confidence: 99%
“…We established intraoral cheek fistulae according to the procedure described previously [27][28][29]. Briefly, the first incision was made in the lateral cheek and another incision was made in the scalp near the ceramic ferrules.…”
Section: Viral Micro-injection and Stereotaxic Surgerymentioning
confidence: 99%
See 1 more Smart Citation